MIC17A is a novel diagnostic marker for feline toxoplasmosis - Jinling Chen; Lilan Xue; Hongxia Hu; Xiaoyan Yin; Hui Cao; Bang Shen (BMC, 2022)
Abstract Toxoplasma gondii is a widespread parasitic pathogen that infect humans and all warm-blooded animals, causing abortion and stillbirth in pregnant women and animals, as well as life threatening toxoplasmosis in immune compromised individuals. Felines are the only definitive hosts of Toxoplasma and oocysts shed by infected felines are the major source of infection for humans and other animals. Given the critical role of felines for T. gondii transmission, control of feline toxoplasmosis has significant impacts on reducing the overall prevalence of animal and human toxoplasmosis. However, reliable diagnosis of feline toxoplasmosis is still challenging. In this study, we found that the putative micronemal protein 17A (MIC17A) that was abundantly expressed in Toxoplasma merozoites is a good diagnostic marker for serological diagnosis of Toxoplasma infection in felines. T. gondii encodes four paralogs of MIC17A in total and the expression of three of them is drastically upregulated in merozoites than in tachyzoites. In contrast, when proteins like GRA1 and MIC3 that are more abundantly expressed in tachyzoites than in merozoites were used as diagnostic antigens to test feline toxoplasmosis, they reacted with Toxoplasma specific IgG antibodies poorly. Taken together, these results suggest that merozoite antigens are better suited for the diagnosis of feline toxoplasmosis than antigens that are highly expressed at tachyzoite or bradyzoite stages.